Design of an Interactive E-Menu Information System Based on QR Code at Kopi Tuku - Chesya Ramadhani Putri Widodo; Mysha Salma Aqila; Nazwa Aulya Asri Pratama; Zatin Niqotaini (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The rapid development of information technology and internet-based services has driven digital transformation in the culinary industry to improve operational efficiency and customer experience. One of the challenges faced by Kopi Tuku is the occurrence of long queues during peak hours due to conventional ordering processes that require customers to view printed menus and place orders directly at the cashier. This study aims to design an interactive QR Code-based E-Menu Information System that can streamline the ordering and payment process while enhancing service efficiency. The research employed the Prototyping Development Model, involving problem identification, data collection, requirements analysis, object-oriented system design using Unified Modeling Language (UML), and user interface prototyping using Figma. The results of the study produced a comprehensive system design consisting of use case diagrams, activity diagrams, sequence diagrams, class diagrams, and interactive user interface prototypes. The proposed system enables customers to access digital menus, place orders, monitor order status, and complete digital payments through their smartphones by scanning QR Codes. The designed system also facilitates transaction verification and order processing by cashiers and baristas in an integrated environment. In conclusion, the QR Code-based interactive E-Menu Information System has the potential to improve service efficiency, reduce customer waiting times, increase order accuracy, and provide a more practical and modern customer experience at Kopi Tuku.